Isoliquiritigenin Inhibits Cigarette Smoke-Induced COPD by Attenuating Inflammation and Oxidative Stress via the Regulation of the Nrf2 and NF-κB Signaling Pathways - Yu, Duo; Liu, Xueshibojie; Zhang, Guangxin; Ming, Zhihui; Wang, Tiejun (Frontiers in Pharmacology, 2018)
Chronic obstructive pulmonary disease (COPD) is the major leading cause of prevalent with high mortality among worldwide. Cigarette smoke (CS) is a main risk factor for COPD. It causes chronic inflammation and oxidative stress contributes to disorder of lung function in COPD. Isoliquiritigenin (ILG), a natural flavonoid derived from the root of liocice, possesses both anti-inflammatory and anti-oxidative activities that may protect against inflammatory diseases. In the present study, we tested the mechanism and protective effect of ILG on CS-induced COPD. Mice were exposed to CS with 5 days a week with 5 cigarettes, 4 times a day with a 10 min smoke free interval between exposures. ILG was given orally. The bronchial alveolar lavage fluid (BALF) was collected for testing the levels of inflammatory cytokines and inflammatory cells. The lung tissues were obtained for evaluating the pathological changes, lung edema, MPO activity, MDA level, as well as the expression of Nrf2 and NF-κB signaling pathways. The results showed that ILG reduced the infiltration of inflammatory cells, and the production of inflammatory cytokines, and reversed the CS-induced lung pathological injuries, lung wet/dry ratio, MPO activity, and MDA level. Further research also showed that ILG dose-dependently up-regulated the expression of Nrf2 and down-regulated the expression of NF-κB signaling pathways induced by CS. In conclusion, ILG protected against CS-induced COPD through inhibiting inflammatory and oxidative stress via regulating Nrf2 and NF-κB signaling pathways, and ILG might be an effective treatment for curing COPD.